T cells and their products in diabetic kidney disease - Liu, Yue; Lv, Yaodong; Zhang, Tingwei; Huang, Tongtong; Lang, Yating; Sheng, Qinghao; Liu, Yingxiao; Kong, Zhijuan; Gao, Ying; Lu, Shangwei; Yang, Meilin; Luan, Yaqi; et al. (Frontiers in Immunology, 2023)
Diabetic kidney disease (DKD) is the most common cause of end-stage renal disease and has gradually become a public health problem worldwide. DKD is increasingly recognized as a comprehensive inflammatory disease that is largely regulated by T cells. Given the pivotal role of T cells and T cells-producing cytokines in DKD, we summarized recent advances concerning T cells in the progression of type 2 diabetic nephropathy and provided a novel perspective of immune-related factors in diabetes. Specific emphasis is placed on the classification of T cells, process of T cell recruitment, function of T cells in the development of diabetic kidney damage, and potential treatments and therapeutic strategies involving T cells.